THE IMPACT OF AI-ORIENTED R&D EXPENDITURES ON CORPORATE REVENUE GROWTH: A CASE STUDY OF MICROSOFT AND GOOGLE COMPANIES (Scientific Journal of Actuarial Finance and Accounting, 2026)
This research paper investigates the impact of artificial intelegence (AI) -related investment on research and development (R&D) expenditures on corporate revenue growth, in the cases of 2 companies: Microsoft and Google. over the period 2022-2025. The main objective of this research is top analyse how investment in technologies particularly Artificial intelligence (AI) and AI-related research and development influence company financial performance. The article is based on financial statement analysis and is conducted using key indicators such as the R&D-to-revenue ratio, revenue growth, total investment, and investment intensity. A comparative and trend analysis approach was applied to assess the relationship between investment strategies and revenue dynamics. The results indicate that both companies are increasing their investment levels, and correspondingly, their revenue indicators are also rising proportionally. While Google outperforms Microsoft in all indicators, Microsoft demonstrates a stable and balanced investment structure.